2011
DOI: 10.1002/adfm.201002444
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Colloidal Heterostructures of Anisotropic Semiconductor Nanocrystals Decorated with Noble Metals: Synthesis and Function

Abstract: This Feature Article offers an overview of hybrid colloidal heterostructures of anisotropic semiconductor nanocrystals decorated with metals; primarily gold and platinum. The nonspherical shapes of the semiconductor components create a great variety of metal-decorated hybrid nanostructures, whose synthesis and morphology are considered here. Due to the current interest in photocatalytic systems able to utilize solar energy for water-splitting, the use of Pt-decorated CdS-based nanorods for hydrogen generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
114
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 73 publications
0
114
0
Order By: Relevance
“…19,[38][39][40][41][42] Colloidal oligomeric hybrid nanoparticles (HNPs) offer the possibility to tailor material combinations for advanced applications in the fields of photocatalysis and (opto-)electronics. 43,44 A number of studies have demonstrated the excellent photo-catalytic properties of metal-semiconductor HNPs in liquid solution, which are based on an efficient separation of photogenerated charge carriers. 45 The electrons move towards the metallic part of the HNPs from where they can be 3 transferred to reducible species in the solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19,[38][39][40][41][42] Colloidal oligomeric hybrid nanoparticles (HNPs) offer the possibility to tailor material combinations for advanced applications in the fields of photocatalysis and (opto-)electronics. 43,44 A number of studies have demonstrated the excellent photo-catalytic properties of metal-semiconductor HNPs in liquid solution, which are based on an efficient separation of photogenerated charge carriers. 45 The electrons move towards the metallic part of the HNPs from where they can be 3 transferred to reducible species in the solution.…”
mentioning
confidence: 99%
“…Pt-semiconductor combinations belong to the most powerful photocatalysts. 44 Despite the plentitude of photocatalytic studies and the often applied description of HNPs as promising candidates for optoelectronic applications, only few studies have investigated their electrical characteristics in solid-state devices in detail. Depending on the combination of materials, the characteristics of HNP thin films vary significantly.…”
mentioning
confidence: 99%
“…H ybrid nanostructures have become an important class of nanomaterials that can allow integration of distinct components (denoted as 'subunits') with different functionalities and have facilitated unique synergistic coupling effects [1][2][3][4][5] . As compared with concentric core-shell configuration whose surface chemistry is merely determined by the outermost shell component and is uniform 6,7 , non-centrosymmetric arrangement of functional subunits in a hybrid nanostructure (denoted as 'nc-HN') can lead to new topological properties because each subunit can provide surface functional moieties with asymmetric synergistic coupling.…”
mentioning
confidence: 99%
“…Among them, i) heterodimers made of spherical domains [29,33,[38][39][40][41][42][43][44], ii) dumbbell-like HYNCs based on the selective growth of domains on one or both tips of a nanorods (NRs) [31,32,34,[45][46][47][48], and iii) other structures such as branched or pyramidal-shaped NCs decorated with several domains [45,49,50]. In all of these cases, the increased and often new functionality coming from the synergetic combination of parent properties allows to expand the already wide applicability of NCs [28,51,52]. HYNCs in which spherical, rod or branched sections are connected in a controlled morphology present promises for a number of potential uses ranging from nanoelectronics to biomedical, photovoltaic and catalytic applications [52][53][54].…”
Section: Hybrid Nanostructuresmentioning
confidence: 99%